QUANTIFICATION OF HEALTH EFFECTS OF EXPOSURE TO AIR POLLUTION (PM10) IN TABRIZ, IRAN - Ghozikali, M. G.; Borgini, A.; Tittarelli, A.; Amrane, A.; Mohammadyan, M.; Heibati, B.; Yetilmezsoy, K. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2016)
Epidemiological studies show that long-term exposure to PM is associated with an increased risk of cancer or cardiovascular and respiratory diseases. The main objective of the present study was the assessment of health outcomes related to PM10 (particulate matter (PM) of aerodynamic diameter <= 10 mu m) exposure in Tabriz, Iran. Related health impacts (relative risk and baselineincidence) due to exposure to PM10 in the city of Tabriz were assessed by using the well-established AirQ2.2.3 model by the World Health Organization European Center for Environment Health. We estimated that out of 15,651 total deaths in the city, 7679 and 1020 people died due to cardiovascular and respiratory related deaths respectively. Among the 19,467 people admitted to hospital due to respiratory disease, 1114 diseases could be attributed to PM10. According to this model, cases of natural mortality, cardiovascular deaths and respiratory mortality caused by PM10 were about 832, 439, and 85, respectively.
Keywords: AirQ2.2.3 Model; Hospital Admissions; Mortality; PM10; Respiratory Disease; LONG-TERM EXPOSURE; PARTICULATE MATTER; QUALITY; CITIES; PARTICLES; COHORT; Environmental Sciences & Ecology